PENINGKATAN KEMAMPUAN VERBAL SISWA –SISWA TK ISLAM BHAKTI 02 SEMARANG MELALUI PENGENALAN UNGKAPAN-UNGKAPAN DASAR SEHARI-HARI DALAM BAHASA INGGRIS - Endang Yuliani Rahayu; Katharina Rustipa; Teguh Kasprabowo; Yulistiyanti, Yulistiyanti; Agnes Widyaningrum (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
English language is not a national language for Indonesian people but as it has an important role in the development of science and technology. For this reason the team has interest to introduce English to Students of Kindergaten in TK Islam Bhakti 02 Semarang mainly the daily expressions and vocabularies that are usually used in certain group of people. Children in the step of Kindergatten are in the golden phase of development that they can easly imitate vocabularies introduced to them, this fact has inspired the team to conduct this public service mainly in TK Islam Bhakti 02 Semarang Kindergatten not the other. By implementing method of listen and repeat and completed with with audio visual facility such as notebook, LCD and speaker active so this publci service have been carried out well and at the end of the session it was always closed with singing to keep the students feel happier and it is also hoped to increase their verbal competance